2017
DOI: 10.1002/jcp.26079
|View full text |Cite
|
Sign up to set email alerts
|

Src nuclear localization and its prognostic relevance in human osteosarcoma

Abstract: Osteosarcoma is the most common malignant bone tumor in children and young adults. The identification of proteins which exhibit different subcellular localization in low- versus high-risk osteosarcoma can be instrumental to obtain prognostic information and to develop innovative therapeutic strategies. Beside the well-characterized membrane and cytoplasmic localization of Src protein, this study evaluated the prognostic relevance of its so-far unknown nuclear compartmentalization. We analyzed the subcellular d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 28 publications
1
23
0
Order By: Relevance
“…Taken together, this evidence suggested that the SFKs could be useful to create an "open" chromatin more accessible to transcriptional factors [52]. In this context, we recently demonstrated the Src nuclear localization in osteoblasts and low aggressive osteosarcoma cells [46], and in particular we observed nuclear Src accumulation in hypocondensated chromatin, as demonstrated by the low DRAQ5 staining (Figure 2). This finding, together with the work by Takahashi, strongly suggests a function for nuclear Src in the regulation of transcription.…”
Section: Regulation Of Gene Transcription and Chromatin Architecturesupporting
confidence: 58%
See 4 more Smart Citations
“…Taken together, this evidence suggested that the SFKs could be useful to create an "open" chromatin more accessible to transcriptional factors [52]. In this context, we recently demonstrated the Src nuclear localization in osteoblasts and low aggressive osteosarcoma cells [46], and in particular we observed nuclear Src accumulation in hypocondensated chromatin, as demonstrated by the low DRAQ5 staining (Figure 2). This finding, together with the work by Takahashi, strongly suggests a function for nuclear Src in the regulation of transcription.…”
Section: Regulation Of Gene Transcription and Chromatin Architecturesupporting
confidence: 58%
“…Indeed, in osteosarcoma and in hormone-positive breast cancer the Src nuclear compartmentalization is associated with improved patients' overall survival. This evidence suggests a sort of physiological relevance for Src nuclear localization, confirmed by the high Src nuclear content observed in normal osteoblasts [46].…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations